A study of K-12 teachers' TPACK on the technology acceptance of E-schoolbag. Issue 7 (3rd October 2021) - Yang, Jinzhong; Wang, Qiyun; Wang, Jingying; Huang, Muxiong; Ma, Yongjun
ABSTRACT: E-Schoolbag is an integrated platform presented on the portable digital devices for educational purposes. Successful and sustainable integration of e-Schoolbag into the classroom often demands teachers to be equipped with essential knowledge, skills, and willingness to employ it on a voluntary basis. The purpose of this study was to examine if teacher's TPACK abilities could predict their inclination to use e-Schoolbag. A total of 1185 teachers from 45 primary and secondary schools in China participated in this study. A structural equation model was established to examine if and how the TPACK framework might affect TAM. Results showed that the teachers' TPACK level had a large impact on their acceptance of e-Schoolbag through perceived usefulness (PU) and ease of use (EOU). Specifically, the technological knowledge (TK) component was more significantly correlated with the e-Schoolbag acceptance than Pedagogical knowledge (PK) and content knowledge (CK). The path coefficient value further showed that TPACK affected the EOU more than the PU.